2017
DOI: 10.1155/2017/5819676
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Squamous Cell Carcinoma Presenting with Streptococcus intermedius Cerebral Abscess

Abstract: Background Cerebral abscess is caused by inoculation of an organism into the brain parenchyma from a site distant from the central nervous system. Streptococcus intermedius (S. intermedius) is a commensal organism that is normally present in the aerodigestive tract and was reported to be the cause of brain abscesses after esophageal dilatation or upper endoscopy. Case Presentation We report the case of a 53-year-old female who presented with hematemesis and melena followed by left-sided weakness. Initially, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The dominance of S. milleri species is consistent with other published UK epidemiological datasets on causative microbiology 7 , 14 , 29 and temporal trends in brain abscess epidemiology. 6 The dominant role of S. intermedius is also exemplified by case reports of brain abscesses [30][31][32][33][34] and noted to be a frequent species in the S. milleri group isolated from central nervous system specimens. 35 Another recent UK case series suggests the ' S. anginosus group' is predominant, but does not provide a breakdown of the S. milleri group by species.…”
Section: Microbiologymentioning
confidence: 96%
“…The dominance of S. milleri species is consistent with other published UK epidemiological datasets on causative microbiology 7 , 14 , 29 and temporal trends in brain abscess epidemiology. 6 The dominant role of S. intermedius is also exemplified by case reports of brain abscesses [30][31][32][33][34] and noted to be a frequent species in the S. milleri group isolated from central nervous system specimens. 35 Another recent UK case series suggests the ' S. anginosus group' is predominant, but does not provide a breakdown of the S. milleri group by species.…”
Section: Microbiologymentioning
confidence: 96%
“…Bacterial migration from esophageal dilation and cancer has been reported as a cause of brain abscesses. 10 - 12 Hanna and Das 10 and Nayfe et al 11 reported 2 cases of brain abscesses caused by Streptococcus intermedius in association with esophageal adenocarcinoma and squamous cell carcinoma, respectively. To the best of our knowledge, our case is the first in the literature to describe brain abscesses caused by Streptococcus intermedius in association with esophageal perforation of unknown etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these different associations, the loss of esophageal mucosal integrity may be the main reason for brain abscess formation rather than the underlying disease. 11 The loss of mucosal integrity may have allowed gut flora to enter the bloodstream and cause bacterial spread to the brain. 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remainder of the cases identified in our literature search were cancer patients who developed S. intermedius abscesses but who had not received radiation treatment. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] One of these patients, like our patient, had tonsillar squamous cell carcinoma; however, this patient presented with a neck abscess before cancer diagnosis. 12…”
Section: Review Of Existing Literaturementioning
confidence: 99%